Implementation of a web application for managing public transport in the city of bunia (Democratic Republic of Congo) - MAKI MUGENYI Daniel Sagesse; MUHINDO KIKENYA Chris; BABONANGENDA BIZIMUNGU Jimmy; ENGANGE PILIPILI Syntiche; MWIRA WAYESU Daniel (International Journal of Scientific Research and Innovative Studies, 2026)
Public transport is a fundamental driver of development in emerging cities, promoting population mobility and supporting economic activity. In Bunia, a city in the Ituri province of the Democratic Republic of Congo, public transport management remains largely manual, characterised by poor organisation, a lack of planning, and difficulties related to data archiving. This situation is particularly evident within the Translux association, a major player in local urban transport. This article proposes the design and implementation of a web application to optimise the management of public transport operations. The methodology adopted is based on needs analysis, UML modelling, development using PHP, and data management via MySQL. The results obtained show a significant improvement in the management of routes, reservations, vehicles, drivers, and fares, while reducing data entry errors and enhancing decision-making transparency. Keywords: public transport, web application, information system, route management, digitalisation. Received Date: December 20, 2025 Accepted Date: January 12, 2026 Published Date: February 01, 2026 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/562